Anmeldelser - Ryom, Peter (Danish Yearbook of Musicology, 1997)
Review of: Michael Talbot: The Sacred Vocal Music of Antonio Vivaldi. Studi di Musica Veneta, Quaderni Vivaldiani 8. Leo. S. Olschki, Firenze 1995.